Effects of ischemic preconditioning on ischemia/reperfusion-induced arrhythmias by upregulatation of connexin 43 expression - Chen Zhenguang; Luo Honghe; Zhuang Mei; Cai Lie; Su Chunhua; Lei Yiyan; Zou Jianyong (Journal of Cardiothoracic Surgery, 2011)
Abstract Background The susceptibility of hypertrophied myocardium to ischemia-reperfusion injury is associated with increased risk of postoperative arrhythmias. We investigate the effects of ischemic preconditioning (IP) on post-ischemic reperfusion arrhythmias in hypertrophic rabbit hearts. Methods Thirty-three rabbit models of myocardial hypertrophy were randomly divided into three groups of 11 each: non-ischemia-reperfusion group (group A), ischemia-reperfusion group (group B), and ischemic preconditioning group (group C). Another ten healthy rabbits with normal myocardium served as the healthy control group. Rabbit models of myocardial hypertrophy were induced by abdominal aortic banding. Surface electrocardiogram (ECG) was recorded and Curtis-Ravingerova score was used for arrhythmia quantification. Connexin 43 (Cx43) expression was assessed by immunohistochemistry. Results Ratios of heart weight to body weight and left ventricular weight to body weight increase significantly in the three groups compared with the healthy control group (p < 0.05). Arrhythmia incidence in group C is significantly lower than group B (p < 0.05). Curtis-Ravingerova score in group C is lower than group B (p < 0.05). Cx43 expression area in group A is smaller by comparison with the healthy control group (p < 0.05). Cx43 expression area and fluorescence intensity in group B are reduced by 60.9% and 23.9%, respectively, compared with group A (p < 0.05). In group C, Cx43 expression area increases by 32.5% compared with group B (p < 0.05), and decreases by 54.8% compared with group A (p < 0.05). Conclusions The incidence of ischemia/reperfusion-induced arrhythmias in hypertrophic rabbit hearts decreases after IP, which plays an important protecting role on the electrophysiology of hypertrophied myocardium by up-regulating the expression of Cx43.